2013
DOI: 10.1177/8755122513500922
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Infectious Diseases Transition Service on the Care of Outpatients on Parenteral Antimicrobial Therapy

Abstract: Background Many hospitalized patients with complicated infections are discharged on outpatient parenteral antimicrobial therapy (OPAT). However, little is known about how to improve the postdischarge care of OPAT patients. Objective The impact of an infectious diseases transitions service (IDTS) on OPAT patient readmissions, as well as on processes of care, was evaluated. Methods We performed a controlled, quasi-experimental evaluation over 15 months in an academic medical center. Intervention-arm patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…The optimal strategy will likely require a coordinated, comprehensive approach from diagnosis to discharge planning and follow-up. Components with the potential to reduce readmissions include an antibiotic stewardship program during the hospitalization and post-discharge (5152), a longitudinal rehabilitation program to mitigate against functional impairments (53), early and frequent follow-up, and timely access to providers to effectively manage new conditions and complications (54). Comparative studies, designed to test the various potential strategies, will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal strategy will likely require a coordinated, comprehensive approach from diagnosis to discharge planning and follow-up. Components with the potential to reduce readmissions include an antibiotic stewardship program during the hospitalization and post-discharge (5152), a longitudinal rehabilitation program to mitigate against functional impairments (53), early and frequent follow-up, and timely access to providers to effectively manage new conditions and complications (54). Comparative studies, designed to test the various potential strategies, will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…Given the likelihood of a new, unresolved, or recurrent infectious process (17), a central aspect of care coordination and discharge planning is antibiotic stewardship (43,44). The effectiveness of this strategy could potentially be augmented with scheduled clinical assessments in person or via home telemonitoring (45).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the benefits of inpatient ID consultation on patient outcomes including 30-day readmissions [ 18 , 19 ]. However, limited available data have not demonstrated a significant reduction in readmissions for OPAT programs [ 20 , 21 ]. In contrast, studies in primary care settings have shown that a transitional care model incorporating phone calls to patients after hospital discharge, early outpatient physician follow-up visits, and clear communication between the inpatient and outpatient treatment teams are associated with improved 30-day readmissions [ 22–25 ].…”
mentioning
confidence: 99%